A Unifying Model for Turbulent Hyporheic Mass Flux Under a Wide Range of Near‐Bed Hydrodynamic Conditions - Chieh‐Ying Chen; Dimitrios K. Fytanidis; Marcelo H. Garcia (Geophysical Research Letters)
Abstract Existing models for estimating hyporheic solute mass flux often require numerous parameters related to flow, bed, and channel characteristics, which are frequently unavailable. We performed a meta‐analysis on existing data set, enhanced with high Reynolds number cases from a validated Computational Fluid Dynamics model, to identify key parameters influencing effective diffusivity at the sediment water interface. We applied multiple linear regression to generate empirical models for predicting eddy diffusivity. To simplify this, we developed two single‐parameter models using either a roughness or permeability‐based Reynolds number. These models were validated against existing models and literature data. The model using roughness Reynolds number is easy to use and can provide an estimate of the mass transfer coefficient for solutes like dissolved oxygen, particularly in scenarios where detailed bed characteristics such as permeability might not be readily available.